The Effect of Sales Promotion and E-Service Quality on Purchase Decisions of Grabfood Users in Cirebon City - Amanda Agustella; Aang Curatman (International Journal of Business, Economics, and Social Development, 2026)
The development of app-based food delivery services has increased competition between platforms, necessitating a deeper understanding of the factors influencing consumer purchasing decisions. Therefore, this study aims to analyze the influence of sales promotions and e-service quality on purchasing decisions among Grabfood users in Cirebon City. This study uses a quantitative method with an associative research approach aimed at examining the relationships and influences between the variables studied. Data for this study were collected through questionnaires distributed to 130 respondents who are active Grabfood users in Cirebon City, selected using a purposive sampling technique. All data obtained were then analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach. The results show that sales promotions have a positive and significant influence on purchasing decisions among Grabfood users, indicating that promotional strategies in the form of coupons, rebates, cashback, and other promotional incentives can increase consumer interest in making purchases. Furthermore, e-service quality has also been shown to have a positive and significant influence on purchasing decisions, indicating that e-service quality such as ease of use of applications, system reliability, speed of service processes, and transaction security play a role in creating a sense of security and comfort for consumers. Simultaneously, the sales promotion and e-service quality variables are able to explain purchasing decisions by 49.6%, while the remainder is influenced by other variables not included in this study. These findings confirm that consumer purchasing decisions can be improved through the implementation of appropriate promotional strategies and supported by continuous improvement in the quality of digital services.